The God-shaped brain : how changing your view of God transforms your life - Jennings, Timothy R., 1961- (Downers Grove, Ill. : InterVarsity Press, 2013)
Psychiatrist Tim Jennings unveils how our brains and bodies thrive when we have a healthy understanding of who God is. He dispels common misconceptions about God and shows how different God concepts affect the brain differently. Our brains can adapt, change and rewire with redeemed thinking that frees us from unnecessary pain and suffering. --from publisher description
God is love -- The human brain and broken love -- The infection of fear -- Freedom to love -- The battle between the conflicting views about God -- Love strikes back -- Engaging the battle - Love stands firm -- Changing our view of God -- The power of truth -- The truth about sin -- Enlarging our view of God -- The judgment of God -- In the brain of Christ -- Forgiveness -- When good prevails -- When love burns free -- Buddha, Jesus and preparing your brain for eternity -- Putting it all together--simple steps to a healthier brain.
Includes bibliographical references and index.
Keywords: God (Christianity); Thought and thinking -- Religious aspects -- Christianity; Christian life; Mental health -- Religious aspects -- Christianity